PENGARUH PENILAIAN PEMBERIAN KREDIT TERHADAP KUALITAS KREDIT (Studi empiris pada KPRI Satria di Isimu Kabupaten Gorontalo) - Arifin Arifin (AkMen JURNAL ILMIAH, 2017)
This study aims to determine how much influence the provision of credit ratings on Credit Quality on Employee Cooperative Republic of Indonesia Satria Isimu Gorontalo regency, either simultaneously or partially. Sampling method used in this research is purposive sampling method, whereas the basic data collection is through a list of questions that tested the validity and reliability through each item to questions in the questionnaire. The analytical method used is multiple regression. The first hypothesis testing results show that the credit ratings simultaneously significant effect on quality of credit of 0.978 or 97.8% (very high category based interpretation Guilford). The results of this study indicate that the proposed model is acceptable and can be explained jointly by the variation of the variable credit ratings. While external variables not examined but also affect the credit quality of 0.022 (2.2%). For example a credit line of professionalism. Results of testing the second hypothesis that the partial credit ratings affect the credit quality of, among others: Character partially positive and significant impact on quality of credit of 0.092 (9.28%); Capacity partially positive and significant impact on quality of credit of 0.128 (12.8%); Capital partially positive and significant impact on quality of credit of 0,270 (27.0%); Collateral partially positive and significant impact on quality of credit of 0.572 (57.2%) and Condition of economi partially positive and not significant to the quality of credit of 0.091 (9.1%)